ANALISIS RASIO KEUANGAN MENGUKUR KINERJA KEUANGAN PT PUPUK ISKANDAR MUDA (MENERAPKAN DATA 2022-2024) - Athaya Nasywa; Jamaluddin Jamaluddin (IndOmera, 2026)
This study aims to measure financial performance using financial ratio analysis in the form of Liquidity Ratio, Profitability Ratio, and Solvency Ratio at PT Pupuk Iskandar Muda. The method used is descriptive with a qualitative approach. The data used is secondary data from PT Pupuk Iskandar Muda's financial statements for 2022-2024. The data collection technique uses documentation techniques. The results of this study indicate that PT Pupuk Iskandar Muda's financial performance based on Liquidity Ratio as measured by the current ratio, quick ratio, and cash ratio is in poor condition because it is below industry standards. Based on Profitability Ratio as measured by return on equity, return on assets, and net profit margin is in poor condition because it is below industry standards. Based on Solvency Ratio as measured by debt to equity ratio and debt to asset ratio is in poor condition because it is above industry standards.